First molecular detection of five gastroenteritis viruses in untreated wastewater and impact of seasonal change on their distribution in Cameroon - Marie Atsama-Amougou; Dowbiss Djomsi-Meta; Modeste Romuald Ngamaleu; Fredy Brice Nemg Simo; Christophe Lontsi Saha; Nadine Lamare-Boutgam; Celestin Godwe; Martin Maidadi-Foudi; Marcel Tongo; Etienne Mpabuka; Charles Kouanfack; Ahidjo Ayouba (One Health, 2025)
Background: Wastewater-based epidemiology has emerged as a valuable tool for surveilling food- and waterborne disease outbreaks. However, wastewater-based epidemiology remains poorly understood in sub-Saharan Africa. The current study investigated the prevalence of five human enteric viruses and the effect of seasonality on their distribution. Materials and methods: A twelve-month cross-sectional study was conducted using untreated wastewater. Collected samples were concentrated by polyethylene glycol precipitation and analyzed for molecular detection of Adenovirus, Noroviruses Genotype I, Noroviruses Genotype II, Rotavirus, and Astroviruses using a commercially available Real-Time PCR Bosphore® Gastroenteritis Panel Kit. Results: Overall, all target viruses were detected, with adenoviruses being the most prevalent at 88.9 % (64/72). Our results revealed the variations in the detection of all these viruses, with detection varying with the change of seasons. Although the difference in detection rates between the rainy and dry seasons did not reach statistical significance in some cases, our results reveal a consistent detection (100 %) across all sampling sites at certain seasons. Adenoviruses exhibited a peak detection period from September to November. Regarding Rotavirus and Norovirus, our findings indicate that they exhibited a peak detection during the short rainy season (March–June), with detection rates of 36.7 % (18/49) and 40.9 % (18/44), respectively. Conclusion: This study provides the first report on the effect of seasonality on the distribution of enteric viruses in wastewater in Cameroon. Our results highlight the importance of considering seasonal variations when designing public health interventions and demonstrate the usefulness of wastewater-based epidemiology in environmental surveillance.